Solution structure of a G-quadruplex bound to the bisquinolinium compound Phen-DC3 - Chung, Wan Jun (2014)
Phen-DC3 is a highly promising compound that specifically targets G-quadruplexes, with potent biological effects observed in vivo. We used NMR spectroscopy to solve the structure of the complex formed between Phen-DC3 and an intramolecular G-quadruplex derived from the c-myc promoter. Structural information revealed that Phen-DC3 interacts with the quadruplex through extensive π-stacking with guanine bases of the top G-tetrad. On the basis of our structure, modifications are proposed for the development of this compound for selective targeting of a specific G-quadruplex conformation.